Study and Evaluation of the Effect of Exhaust Heat Recovery Tube Structure on the Efficiency of Heat Recovery in a Sea Water to Fresh Water Distillation System - Khong, Vu Quang; Nguyen, Duy Tien; Vu, Minh Dien; Nguyen, The Truc; Le, Manh Toi; Le, Dang Duy; Ho, Van Dam (Old Journal, 2020)
Energy and fuel are the most important factors affecting the progression of countries worldwide. However, fossil fuel reserves were forecasted to be exhausted in the near future. Therefore, managing and improving energy usage efficiency has been a major challenge. Regarding the internal combustion engine, utilizing waste heat sources (from coolant, exhaust gas) is a simple solution and an effective method in improving engine heat efficiency. This paper will demonstrate the simulation research results by Ansys Fluent Program to optimize the structure of the exhaust heat recovery tube in the system of utilizing exhaust and coolant heat to distill fresh water from seawater. The outcomes show that the heat exchange area and heat transfer coefficient are two important parameters, which directly affect the heat recovery efficiency. With a reasonable structure, the exhaust heat recovery efficiency can archive 10.44%, thus heat usage efficiency of the internal combustion engine can increase from 32.09% to a peak of 42.53%. In addition, predicting heat recovery efficiency will be a fundamental base of upcoming researches to determine other specifications of the seawater to the freshwater distillation system.